Carat USA : an e-mail gaffe and reputational furor (A) - Husack, Daniel; Knoblauch, Kurt; Schwarber, Christopher; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
As Carat USA was in the process of implementing a restructuring plan, a top HR executive accidentally forwarded the communication plan to the entire company via email. The confidential document included the firms messages to employees, clients, vendors and other stakeholders. How can Carat USA recover from the mistake and restore its reputation?
Originally published in Husack, D., Knoblauch, K., Schwarber, C., & ORourke, J. S. (2009). Carat USA: An e-mail gaffe and reputational furor (A). 09-07 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Carat USA; Business communication; Communication planning; Corporate image